2016
DOI: 10.1182/blood-2016-03-706028
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal abnormalities and neutrophil dysfunction in WDR1 deficiency

Abstract: Cell motility, division, and structural integrity depend on dynamic remodeling of the cellular cytoskeleton, which is regulated in part by actin polymerization and depolymerization. In 3 families, we identified 4 children with recurrent infections and varying clinical manifestations including mild neutropenia, impaired wound healing, severe stomatitis with oral stenosis, and death. All patients studied had similar distinctive neutrophil herniation of the nuclear lobes and agranular regions within the cytosol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 20 publications
9
108
0
Order By: Relevance
“…Unexpectedly, we found that loss of WDR1 down-regulates P-Cofilin in all examined cells. Consistent with this, a very recent report showed that P-Cofilin is decreased in the cells of some patients with Wdr1 mutation (45). Interestingly, WDR1 seems to be present in an excessive amount in the cells, which well explains the discrepancies of Cofilin phosphorylation levels observed in knockdown and KO cells (36).…”
Section: Discussionsupporting
confidence: 71%
“…Unexpectedly, we found that loss of WDR1 down-regulates P-Cofilin in all examined cells. Consistent with this, a very recent report showed that P-Cofilin is decreased in the cells of some patients with Wdr1 mutation (45). Interestingly, WDR1 seems to be present in an excessive amount in the cells, which well explains the discrepancies of Cofilin phosphorylation levels observed in knockdown and KO cells (36).…”
Section: Discussionsupporting
confidence: 71%
“…Three reports have been published identifying children with autosomal recessive missense mutations in the WDR1 gene. WDR1 deficient patients have frequent infections, severe stomatitis, and impaired wound healing . Their neutrophils have elevated basal F‐actin levels with impaired spreading, polarization, adhesion, and chemotaxis .…”
Section: Human Disease Caused By Regulators Of the Actin Cytoskeletonmentioning
confidence: 99%
“…Examples of these discoveries are those caused by autosomal or hemizygous recessive mutations in BCL10 11 , CD70 12, 13 , CTPS1 14 , DOCK2 15 , MSN 16 , NIK 17 , RASGRP1 18 , RLTPR 19 , and TRFC 20 ; haploinsufficient mutations in IKAROS 21 or NFKB1 22 ; as well as a heterozygous dominant negative mutation in BCL11B 8 . Other examples include humoral immunodeficiency accompanying multi-organ autoimmunity caused by haploinsufficient mutations in CTLA4 23, 24 or gain-of-function mutations in STAT3 25 ; as well as neutrophil dysfunction caused by autosomal recessive mutations in JAGN1 26 or WDR1 27 . For the most part, these discoveries have dovetailed with findings previously made in mice but have revealed important aspects of the infectious context in which humans manifest disease.…”
Section: Humans: a New Preferred Model Organism For Studying Immunitymentioning
confidence: 99%